2020
DOI: 10.14444/6072
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Sacroiliac Joint Fusion: The Current Evidence

Abstract: Background: Fusion of the sacroiliac (SI) joint as a treatment for low back pain remains controversial. The purpose of this manuscript is to review the current literature and clinical outcomes of SI joint fusion surgery. Methods: We conducted a literature review and included studies with the term ''sacroiliac joint fusion'' that had at least 12 months of clinical follow-up, reported on minimally invasive techniques, and included patient-reported outcome measures. Results: Two approach types (dorsal and lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 50 publications
2
62
0
1
Order By: Relevance
“…159 Reviews Several reviews (narrative, systematic, and metaanalysis) have been published focusing on lateral transiliac MIS SIJF with transfixing devices. [186][187][188][189][190][191][192][193] These reviews support the previously stated conclusions, including that lateral MIS SIJF is beneficial (proven improvements in pain and function) in appropriately selected patients with SIJ pain.…”
Section: Level IV Studiessupporting
confidence: 75%
See 1 more Smart Citation
“…159 Reviews Several reviews (narrative, systematic, and metaanalysis) have been published focusing on lateral transiliac MIS SIJF with transfixing devices. [186][187][188][189][190][191][192][193] These reviews support the previously stated conclusions, including that lateral MIS SIJF is beneficial (proven improvements in pain and function) in appropriately selected patients with SIJ pain.…”
Section: Level IV Studiessupporting
confidence: 75%
“…The posterior (dorsal) MIS SIJF procedure is a recognized and well-described distinct surgical procedure. 192,193,215 In the dorsal approach, allograft bone products or devices are placed into the ligamentous portion of the joint via dissection of the multifidus muscle and removal of a portion of the ligaments covering the dorsal, posterior aspect of the joint. A portion of the interosseous SIJ ligament is also typically removed.…”
Section: Posterior (Dorsal) Mis Procedures Procedures Descriptionmentioning
confidence: 99%
“…Martin et al conducted a meta-analysis by assessing the impact of minimally invasive surgery for SIJ fusion on VAS and ODI, and found that both PROMs had significantly reduced ( p < 0.05 for VAS and ODI) implying a significant improvement in pain as well functional outcomes of patients undergoing these procedures. Statistical analysis was not conducted against open SIJ fusion, nor between the different options for minimally invasive surgery [ 106 ]. A randomised controlled trial conducted by Dengler et al compared the iFuse minimally invasive technique against conservative management for pain secondary to SIJ dysfunction, and found that those managed surgically had significantly improved VAS ( p < 0.001), ODI ( p < 0.001) and EuroQol 5-Dimension (EQ-5D) ( p < 0.001) 24 months post-procedure [ 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…A Limitation of this review is that the majority of the data is retrospective and mainly where involving the iFuse Implant system. 78 …”
Section: Surgical Treatment Optionsmentioning
confidence: 99%